2013
DOI: 10.1016/j.neulet.2013.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Regional cerebral blood flow alterations in obstructive sleep apnea

Abstract: Obstructive sleep apnea (OSA) is a condition characterized by upper airway muscle atonia with continued diaphragmatic efforts, resulting in repeated airway obstructions, periods of intermittent hypoxia, large thoracic pressure changes, and substantial shifts in arterial pressure with breathing cessation and resumption. The hypoxic exposure and hemodynamic changes likely induce the structural and functional deficits found in multiple brain areas, as shown by magnetic resonance imaging (MRI) procedures. Altered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 34 publications
(48 reference statements)
1
40
0
Order By: Relevance
“…Magnetic resonance spectroscopy demonstrated that hypoxia-related metabolites and microstructural changes in the putamen are more pronounced with increasing SA severity 31. Furthermore, decreased cerebral blood flow was reported in the right red nucleus and right midbrain of patients with SA 32. These abnormal findings in the basal ganglia and midbrain of patients with SA may indicate an association between SA and the risk of PD.…”
Section: Discussionmentioning
confidence: 93%
“…Magnetic resonance spectroscopy demonstrated that hypoxia-related metabolites and microstructural changes in the putamen are more pronounced with increasing SA severity 31. Furthermore, decreased cerebral blood flow was reported in the right red nucleus and right midbrain of patients with SA 32. These abnormal findings in the basal ganglia and midbrain of patients with SA may indicate an association between SA and the risk of PD.…”
Section: Discussionmentioning
confidence: 93%
“…In patients with OSA, this leads to nocturnal apneas and hypopneas, intermittent hypoxia, reoxygenation and hyper-/hypocapnia events, along with sleep fragmentation, and changes in cerebral blood flow (Baril et al, 2015, Shiota et al, 2014, Yadav et al, 2013). The prevalence of OSA is noticeable in general population and around 50% in patients with cardiovascular or metabolic disorders (Khazaie et al, 2013, Khazaie et al, 2011, Lévy et al, 2015, Lurie, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated muscle sympathetic nerve activity (MSNA) correlates with altered Blood Oxygen-Level-Dependent (BOLD) signals in the midbrain in OSA, suggesting a midbrain role in eliciting the high sympathetic tone in the sleep disorder (Fatouleh et al, 2014; Lundblad et al, 2014). CBF is decreased in the right midbrain of OSA subjects (Yadav et al, 2013), which may reflect lower perfusion demand, perhaps from an altered functional state (for example, lower tonic activity), or impaired cerebral perfusion. Structural changes consistent with inflammatory or glial changes, namely diffusion decreases and volume increases, appear in the hypothalamus in OSA (Lundblad et al, 2014; Tummala et al, 2016), which projects heavily to the midbrain (Sakuma and Tada, 1984; Thompson and Swanson, 1998).…”
Section: Introductionmentioning
confidence: 99%